36,28×(6,7-4,5)
tính bằng cách thuan tien a 4,5 nhân 6,7+6,7 nhân 6,5-6,7
\(4,5\times6,7+6,7\times6,5-6,7\)
\(=6,7\times\left(4,5+6,5-1\right)\)
\(=6,7\times10\)
\(=67\)
Ta có:\(4,5\times6,7+6,7\times6,5-6,7\)
\(=\left(4,5+6,5-1\right)\times6,7\)
\(=10\times6,7\)
\(=67\)
4,5 * 6,7 + 6,7 * 6,5 - 6,7
= 6,7 * (4,5 + 6,5 - 1 )
=6,7 * 10
=67
4,5/6,7=
4,5+3,4+6,7+1,3+3,5=?
4,5+3,4+6,7+1,3+3,5
=(4,5+3,5)+(6,7+1,3)+3,4
=8+8+3,4
=19,4
Chúc bạn học giỏi nha!!!
mik trả lời đầu tiên đó, bạn nhớ k nha
4,5+3,4+6,7+1,3+3,5
=(4,5+3,5)+(6,7+1,3)+3,4
=8+8+3,4
=8x2 +3,4
=16+3,4
=19,4
A=4,5*(200-49)-(3,2+1,3)*50-(6,7-2,2)
tinh nhanh :1,2 + 2,3 +3,4 +4,5 +5,6 +6,7 +7,8 +8,9 +9,1
1,2 + 2,3 + 3,4 + 4,5 + 5,6 + 6,7 + 7,8 + 8,9 + 9,1
= ( 1,2 + 7,8 ) + ( 2,3 + 6,7 ) + ( 3,4 + 5,6 ) + 4,5 + ( 8,9 + 9,1 )
= 9 + 9 + 9 + 4,5 + 18
= 49.5
1,2 + 2,3 +3,4 +4,5 +5,6 +6,7 +7,8 +8,9 +9,1=(1,2+7,8)+(2,3+6,7)+(3,4+5,6)+(9,1+8,9)+4,5=9+9+9+18+4,5=27+22,5=49,5
tinh nhanh :1,2 + 2,3 +3,4 +4,5 +5,6 +6,7 +7,8 +8,9 +9,1
(1.2+7.8)+(2.3+6.7)+(3.4+5.6)+(8.9+9.1)+4.5
=9+9+9+18+4.5
=9*3+18+4.5
=27+18+4.5
=45+4.5
49.5
Tính nhanh : 1,2 + 2,3 + 3,4 + 4,5 + 5,6 + 6,7 +7,8 + 8,9 + 9,1
1,2 + 2,3 + 3,4 + 4,5 + 5,6 + 6,7 + 7,8 + 8,9 +9,1
= ( 1,2 + 7,8) + ( 2,3 +6,7) + (3,4+5,6) + ( 8,9 + 9,1 ) + 4,5
= 9 + 9 + 9 + 18 + 4,5
=49,5
1 , 2 + 2 , 3 + 3 , 4 + 4 , 5 + 5 , 6 + 6 , 7 + 7 , 8 + 8 , 9 + 9 , 1
= ( 1 , 2 + 7 , 8 ) + ( 2 , 3 + 6 , 7 ) + ( 3 , 4 + 5 , 6 ) + ( 8 , 9 + 9 , 1 ) + 4 , 5
= 9 + 9 + 9 + 18 + 4 , 5
= 9 + 9 + 9 + 9 + 9 + 4 , 5
= 9 x 5 + 4 , 5
= 45 + 4 , 5
= 49 , 5
1,2 + 2,3 + 3,4 + 4,5 + 5,6 + 6,7 +7,8 + 8,9 + 9,1 =
(1,2 +7,8)+ (2,3+6,7)+(3,4+5,6)+(8,9 + 9,1)+4,5=
9 + 9 + 9 + 18 + 4,5 = 49 . 5
+_
Tính:
1,2 - 2,3 + 3,4 - 4,5 + 5,6 - 6,7 + 7,8 - 8,9 + 9,1
1,2-2,3+3,4-4,5+5,6-6,7+7,8-8,9+9,1
=9,1-(8,9-7,8)-(6,7-5,6)-(4,5-3,4)-(2,3-1,2)
=9,1 - 1,1 - 1,1 - 1,1 - 1,1
=9,1-1,1x4
=9,1-4,4
=4,7
Tính:
1,2 - 2,3 + 3,4 - 4,5 + 5,6 - 6,7 + 7,8 - 8,9 + 9,1